A comprehensive review on mechanical failures cause vibration in the gas turbine of combined cycle power plants. (April 2022) - Watban Khalid Fahmi, Al-Tekreeti; Reza Kashyzadeh, Kazem; Ghorbani, Siamak
Highlights: Unwanted vibration is the main cause of the mechanical breakdown of the gas turbine in the Combined Cycle Power Plants. Unbalancing of the rotor shaft is the most common reason in rotary machine vibration. Eliminating sources of high-energy vibrations reduces machine power consumption. Thermal effects caused by rubs result in spiral vibrations in rotary machines. Resonant vibrations induce High Cycle Fatigue (HCF) affecting the service life of the turbine blade. Abstract: The vibration phenomena which occur in rotary machines, such as power plants, can result in catastrophic consequences. Any failure in any power plant section can result in extended downtime and high repair expenses. Vibration is one of the most common causes of power plant failure. The above-mentioned issues can be avoided using high-accuracy vibration detection and prediction technologies. Therefore, further research into the primary causes of vibration on Combined Cycle Power Plants (CCPPs) can help improve the present vibration evaluation methodologies for power plants. This paper aims to survey some of the most commonly reported factors that can induce vibration in the gas turbine of CCPP. Therefore, this paper aims at reviewing the unbalancing and misalignment, contact among rotating and stationary components (rubbing), steam flow fluctuations, the rotor critical speed, and shorted-turns, which are some of the most common destructive vibrations in this industry. Furthermore, some of the most used well-known technologies for vibration monitoring and evaluation in the gas turbine of CCPPs are described, such as proximity probes, laser Doppler vibrometer, eddy current sensor, and accelerometer, which can be used to create a maintenance time schedule for the gas turbine of CCPPs and also, it helps to reduce maintenance time and power generation costs.